THANKS FROM FULL MAN - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
John C Quachieh, Beckwai Ashanti, Ghana, referring to books received from CTA: 'My home is now a research library, where all sorts of people, especially literate farmers, extension officers, and social workers come. I am scheduled to receive an...